2011
DOI: 10.1002/lary.22501
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hereditary hemorrhagic telangiectasia with submucosal and topical bevacizumab therapy

Abstract: Intranasal submucosal bevacizumab effectively treats HHT-associated epistaxis for up to 12 months following treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 14 publications
1
81
0
Order By: Relevance
“…Patients were carefully followed for nasal cartilaginous septum perforations which have been described as a side effect of intravenous bevacizumab in cancer patients. [18][19][20][21] This complication was also described after bevacizumab submucosal injections 14,22 or laser treatments but never with topical treatments. In this study, nasal cartilaginous septum perforation was not observed following treatment administration.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Patients were carefully followed for nasal cartilaginous septum perforations which have been described as a side effect of intravenous bevacizumab in cancer patients. [18][19][20][21] This complication was also described after bevacizumab submucosal injections 14,22 or laser treatments but never with topical treatments. In this study, nasal cartilaginous septum perforation was not observed following treatment administration.…”
Section: Discussionmentioning
confidence: 97%
“…In the literature, several case reports and pilot studies reported a potential effect of bevacizumab nasal spray on epistaxis in HHT, with different doses and frequency of administration. 13,14,22,25 However, the frequency of epistaxis is highly variable in a given patient and between patients and it is currently not possible to conclude on efficacy based on those reports. We can hypothesize that a one-day treatment is not enough to act on epistaxis and that a single drug administration does not expose nasal mucosal tissue to bevacizumab in levels sufficient to improve epistaxis.…”
Section: Discussionmentioning
confidence: 99%
“…A multitude of treatment options have been proposed to control epistaxis including hormonal manipulation, 6 systemic or topical bevacizumab, 7,8 28 A study by Hitchings et al 29 comparing the impact of nasal closure, argon laser, and a combination of septodermoplasty and argon laser treatments on quality of life, as measured by the 36-Item Short Form Health Survey (SF-36), demonstrated a significant improvement in physical functioning and general health perception for patients undergoing nasal closure.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, serum VEGF is reportedly increased in HHT patients, although levels do not correlate with disease severity [100][101][102]. Administration of Bevacizumab (Avastin Ò ), a VEGF antibody, can ameliorate liver AVMs [103][104][105] and reduce epistaxis [106][107][108][109][110][111][112], although a recent Phase I clinical trial (nasal spray administration) disappointingly showed no efficacy in the treatment of epistaxis [113]. Thalidomide is a second HHT therapeutic that targets angiogenesis.…”
Section: Medical Therapies For Hht: Current Practice and Future Perspmentioning
confidence: 98%